Awakening To Soma Heliakon: Encountering Teacher-Researcher-Learning in the Twenty-First Century - Sameshima, Pauline; Sinner, Anita (Canadian Journal of Education/Revue canadienne de l’éducation, 2009)
As two teacher educators and researchers, we explored dimensions of instructional practice in teacher education through online forums. In the course of this research, we drew upon our online interactivity as the basis for reflexive inquiry. Analysis entailed coding key themes to create a four-part rendering involving a hyperlinked poem, a video, a parallaxic praxis research model, and a tagcloud. Interpreting experience through integrated multimedia examples potentially increases learning engagement and provides insights to our belief that teacher education must be deeply mindful, reflective, and interconnected to living. Key words: teacher education, reflexive inquiry, poetic inquiry, parallaxic praxis Les auteures, deux didacticiennes et chercheuses, l’une à la Washington State University et l’autre à l’University of British Columbia, ont exploré diverses facettes des méthodes utilisées dans la formation à l’enseignement à l’aide de forums de discussion. Au cours de cette recher- che, elles se sont appuyées sur leur interactivité en ligne pour nourrir leurs réflexions. Leur ana- lyse comportait le codage des principaux thèmes en vue de créer une représentation quadriparti- te : poème hyperlié, vidéo, modèle de recherche axé sur la parallaxe et nuage de mots clés. L’interprétation des expériences à travers des exemples de multimédia peut favoriser l’implication dans l’apprentissage et s’inscrit dans le droit fil d’une formation à l’enseignement qui, selon les auteures, doit faire place à la réflexion et être branchée sur la vie. Mots clés : formation à l’enseignement, analyse réflexive, analyse poétique, parallaxe.